Self-enforcing environmental agreements and capital mobility - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2013)
In a multi-country model with mobile capital and global pollution this paper analyzes the stability of self-enforcing environmental agreements (IEAs) when the coalition formed by the signatory countries plays Nash. In accordance with previous environmental literature we show that there exists a unique self-enforcing IEA consisting of two or three signatory countries if emissions tax rates are strategic substitutes. However, emissions tax rates are strategic complements if the pollution is not too detrimental. In that case we find very small self-enforcing IEAs, as before, but now the socially optimal agreement among all countries may be self-enforcing as well. Special emphasis is placed on the investigation and interpretation of the conditions which render stable the grand coalition.
Keywords: H23; H77; Q58; 330; capital mobility; self-enforcing environmental agreements; emissions tax; Nash behavior